Simple fuzzy classification of metal qualities of Ona River, Ibadan, Nigeria, and its implication for fish production and other uses - Olayiwola Akin Akintola; Foluso Oyedotun Agunbiade; Tolulope Omolayo Ariyomo; Toju Esther Babalola; Bolaji Adelanke Adabembe; Oluwaseun Temitope Faloye; Opeyemi Samuel Sajo (Discover Water)
Abstract Elevated concentrations of metals in rivers can pose significant risks to human health. Consequently, it is essential to monitor metal levels in river water to minimize human exposure, particularly through consumption of harvested fish and other uses. This study examined the water quality of the Ona River in Ibadan, Nigeria. Seven potentially toxic elements (PTEs), namely Fe, Cu, Mn, Zn, Pb, Cd, Cr and four macronutrients: Mg, Na, K, Ca were investigated. Surface and pore water samples were collected from six sampling points during the peak of the dry and the rainy seasons. These were analyzed according to standard procedures and processed using the Simple Fuzzy Classification (SFC) model with four classes. The results revealed that the PTEs: Fe, Pb, Cd, Cr, and Mn were detected above guideline limits in several sampling points, indicating possible contamination from anthropogenic sources. Simple fuzzy classification puts the quality of water in the investigated portion of the river in the range of 67.4–88.5% in the C1 (pristine) category during the dry season and 61.9–88.6% in C1 (pristine) during rainy season. However, there were membership functions of up to 58.7 and 63.2; 61.2 and 75.4 as well as 44.3 and 43.5% in C2, C3, and C4 categories (contaminated, polluted and extremely polluted, respectively) during the first and second sampling, respectively. Due to the high concentrations of toxic and bioaccumulative metals in the river, efforts should be made to control the discharge of pollutants into the river. These will prevent human health exposure risks tendencies for various uses, including fish production.